Developing an efficient anticorrosive system through advanced modification of plasma-electrolyzed MgO with CeNiLDH complexed with V₂O₅ nanoparticles and (2E)-But-2-enedioic acid - Mosab Kaseem; Ananda Repycha Safira; Mohammad Aadil; Talitha Tara Thanaa; Arash Fattah-alhosseini (Journal of Magnesium and Alloys)
Advanced hybrid materials with unique properties are essential for addressing the demands of increasingly complex applications. Despite their importance, the self-assembly of layered double hydroxides (LDH) with metallic oxide nanoparticles and dicarboxylic acids is constrained by a limited understanding of the formation mechanisms and difficulties in evaluating their anticorrosive performance. In this study, we developed a novel anticorrosive system by intercalating CeNiLDH with a complex of vanadium pentoxide (V₂O₅) nanoparticles and (2E)‑but-2-enedioic acid ((2E)-BDA) on a MgO layer created through plasma-electrolysis of AZ31 Mg alloy. This system was compared with LDH films intercalated with either V₂O₅ or (2E)-BDA alone. The intercalation of LDH with V₂O₅ and (2E)-BDA resulted in a flower-like structure, while modification with their complex led to a more compact, cloud-like formation. These cloud-like structures, driven by enhanced absorption and robust hydrogen bonding throughout the hierarchical network, effectively suppress corrosion by delaying the movement of corrosive anions. This was reflected in a polarization resistance of 1.51 × 10¹⁰ Ω·cm², which is approximately two orders of magnitude times higher than the resistance of the unmodified LDH film (3.41 × 10⁸ Ω·cm²). Additionally, the corrosion current density (icorr) of the VOBDA sample showed a decrease by four orders of magnitude compared to the unmodified LDH sample, emphasizing the superior anticorrosive performance of this hybrid coating. Density functional theory (DFT) was used to elucidate the bonding and formation mechanisms between LDH and the inorganic-organic complex.